Simple Living and Sustainable Consumption - Kronenberg, Jakub; Iida, Natsuyo (Problemy Ekorozwoju, 2011)
After a brief reference to the philosophical background of simple living and its basic ideas, we explore how simple living can aid sustainable consumption. We look at general linkages between the two concepts and suggest how simple living can be used to support sustainable development (what elements to promote, what policy instruments to use, what barriers may be encountered). We conclude that philosophical reflection is the most important element of simple living that might enrich the current debate on sustainable consumption and suggest how to further strengthen the popularity of simple living movement.